Analisis Kesesuaian Kawasan Wisata Hutan Mangrove Berbasis Ekowisata di Desa Sanleko Kabupaten Buru - Kasmin Suneth; Pieter Th. Berhitu; Adnan Affan Akbar Botanri (ELASTICITY: Journal of Applied Engineering Science, 2024)
Sanleko Village is one of the villages in Namlea District, Buru Regency, Sanleko Village has mangrove potential on its coastline covering an area of 16.21 Ha. Judging from the current tourism conditions in the field, it is very minimal in terms of the development of tourism activities. The role of the community in the development of tourism has not been maximized from the access to bridges in mangroves that have been broken and potholes, the lack of facilities and infrastructure to support tourism. This study aims to determine the suitability of ecotourism-based mangrove forest tourism areas in Sanleko Village, Buru Regency. This study uses descriptive analysis methods and regional suitability analysis. The result obtained is that the conditions for mangrove forest tourism in Sanleko Village have beauty in the mangrove forest, in addition to that in front of the mangrove tourism there is a long sand beach. However, facilities and infrastructure such as roads made of wood and bamboo as bridges in mangrove tourism are not suitable for use. The total score results showed that the IKW values at observation stations 1.2, and 3 were 81.16%, 81.16% and 73.91%, respectively, and belonged to the S1 category (Very Appropriate). Which means that Sanleko Village mangrove tourism can be developed as Mangrove Ecotourism